"Esse é o meu patikula": uma etnografia do dinheiro e outras coisas entre os Kalapalo de Aiha - Novo, Marina Pereira (2017)
This thesis deals with some transformations occurred among the Kalapalo, based on an ethnographic study carried out over the last decade in the Aiha village, located in the southeastern portion of the Xingu Indigenous Land. The increased availability of patikula resources (as opposed to what is “of the community”) originated from cash transfer policies and social security benefits, promoted changes in the village’s daily life as so as the peoples’ who live there. Now they have more access to food or industrialized objects, or even travel more frequently to cities. However, although this is a moment when the transformations are very intense, this thesis tries to show how this process finds its roots in the kalapalo way of dealing with alterity. In this case, it is not possible to talk about “generalized predation”, but nor does it mean avoidance of the relationship with the Other. In this sense, I show how the desire category, on the one hand, mobilizes people towards otherness and, on the other hand, contributes to the creation and strengthening of kinship and friendship networks. I conclude with an ethnographic presentation of the uluki, the main exchange ritual in the region. With this presentation, I point out that just as people create relationships among themselves through the circulation of “things”, the same is true for the villages that make up the so-called “xinguan system”, through the rituals.